ANTIHYPERURISEMIA ACTIVITY TEST OF ETHANOL EXTRACT FROM LEAVES OF KLUWIH (Artocarpus altilis (Parkinson) Fosberg) AGAINST MALE MICE (Mus musculus) - Wajdie, Farid; Kartika, Rudi; Saleh, Chairul (Jurusan Kimia FMIPA UNMUL, 2018)
Phytochemical screening on ethanol extract from leaves of kluwih (Artocarpus altilis (Parkinson) Fosberg) has been carried out and that results showed the presence of flavonoids, alkaloids, phenolic, triterpenoids and steroids. The ethanol extract from leaves of kluwih (Artocarpus altilis (Parkinson) Fosberg) was tested for its antihyperuricemic experimentally in the laboratory with doses of 28 mg/kg, 56 mg/kg and 112 mg/kg which were done orally in male mice (Mus musculus) for the purpose of antihyperuricemic assess the effect of the decrease uric acid in male mice. Uric acid measurements carried out on days 0, 15, 17, 19, 21, 23, 25 and 27 by using uric acid strip and uric acid meter. Treatments with dosage variation kluwih leaves extract (Artocarpus altilis (Parkinson) Fosberg) shows that a dose of 112 mg/kg give blood uric acid levels decrease by 64.23%. The results of this study showed a decrease in uric acid levels as a result of ethanol extract from leaves of kluwih (Artocarpus altilis (Parkinson) Fosberg).